Synergistic and Toxicity-reducing Effects of Periplaneta americana Extract CⅡ-3 Combined with CTX on H22 Tumor Bearing Mice - Yuan, Rui; Liu, Guangming; Guo, Meixian; Liu, Xiaobo (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Cyclophosphamide (CTX) is widely used in tumor treatment, but its clinical therapeutic effect is not ideal due to many side effects. Materials and Methods: In the present study, we researched the synergistic and attenuating effects of CⅡ-3 combined with CTX and their underlying mechanism in H22 tumor-bearing mice. Firstly, we established an H22 tumor-bearing mice model, and the body weight, tumor weight, and survival time were recorded. Secondly, HE staining of tumor tissue was performed, and the related organ index, NK cell killing activity, peripheral blood cells, and bone marrow nucleated cells were measured. Moreover, the changes in IL-6 and IFN-1β in serum were detected by ELISA. Finally, RT-qPCR and Western Blot were performed to detect the expressions of TLR4, TLR9 and NF-κB in tumor tissue. Results: The treatment of CⅡ-3 combined with CTX could increase life extension rate of H22 tumor-bearing mice, reduce tumor weight. Additionally, it could inhibit tumor cell proliferation, increase thymus and spleen index, enhance the activity of T cells in spleen, promote the killing activity of NK cells, and had a certain ameliorate effect on the reduction of WBC, Neut, LYM and bone marrow nucleated cells caused by CTX. And the expression of mRNA and the protein of TLR4, TLR9 and NF-κB in tumor mass of H22 tumor-bearing mice were down-regulated. Conclusion: There were synergistic and attenuating effects of CTX combined with CⅡ-3 in the treatment of tumor and the effects might be mediated by the TLR4/NF-κB and TLR9/NF-κB signaling pathways.
Keywords: Anti-tumor; Cyclophosphamide; Immune depression; Periplaneta americana; Synergism and attenuation